2019
DOI: 10.1002/jsfa.9615
|View full text |Cite
|
Sign up to set email alerts
|

Control of antioxidant efficiency of chlorogenates in emulsions: modulation of antioxidant interfacial concentrations

Abstract: BACKGROUND Controlling the interfacial concentrations of antioxidants (AOs) in oil‐in‐water emulsions can be regarded as a unique approach for increasing the efficiency of AOs in inhibiting the oxidation of lipids. Classical methods to determine the AO distribution in binary systems cannot be employed and their distribution needs to be assessed in the intact emulsion. RESULTS We have employed a well‐established kinetic method to determine the distribution of a homologous series of AOs derived of chlorogenic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 36 publications
(123 reference statements)
7
37
0
Order By: Relevance
“…In attempting to understand this non-linear trend, the distribution of a series of AOs derived from hydroxytyrosol, caffeic acid, gallic acid, protocatechuic acid and chlorogenic acid in intact olive oil, soybean oil and corn-inwater emulsions was determined by employing a pseudophase kinetic model. We demonstrated that there is a positive correlation between the efficiency of AOs and the % of AO at the interfacial region of emulsions (Almeida et al, 2016;Costa et al, 2015;Losada-Barreiro, Bravo-Díaz, Paiva-Martins, & Romsted, 2013;Losada-Barreiro, Sánchez-Paz, & Bravo-Díaz, 2013;Meireles et al, 2019;Silva, Losada-Barreiro, Paiva-Martins, & Bravo-Díaz, 2017). This fundamental result implies that the efficiency of AOs can be, in principle, increased by fine-tuning their interfacial concentrations.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In attempting to understand this non-linear trend, the distribution of a series of AOs derived from hydroxytyrosol, caffeic acid, gallic acid, protocatechuic acid and chlorogenic acid in intact olive oil, soybean oil and corn-inwater emulsions was determined by employing a pseudophase kinetic model. We demonstrated that there is a positive correlation between the efficiency of AOs and the % of AO at the interfacial region of emulsions (Almeida et al, 2016;Costa et al, 2015;Losada-Barreiro, Bravo-Díaz, Paiva-Martins, & Romsted, 2013;Losada-Barreiro, Sánchez-Paz, & Bravo-Díaz, 2013;Meireles et al, 2019;Silva, Losada-Barreiro, Paiva-Martins, & Bravo-Díaz, 2017). This fundamental result implies that the efficiency of AOs can be, in principle, increased by fine-tuning their interfacial concentrations.…”
Section: Introductionmentioning
confidence: 69%
“…This is due to the possibility to fine-tune the hydrophobicity of a polyphenol by the grafting alkyl chains of different length and should help us to understand how antioxidant properties are affected by the hydrophobicity. To date, evidence supporting using different phenolipid series such as rosmarinates (Laguerre et al, 2010), hydroxytyrosyl esters (Almeida et al, 2016;Medina, Lois, Alcántara, Lucas, & Morales, 2009), caffeates (Costa, Losada-Barreiro, Paiva-Martins, Bravo-Díaz, & Romsted, 2015) and chlorogenates (Meireles et al, 2019) in various oil-in-water emulsions has established that there is a nonlinear trend between hydrophobicity and antioxidant efficiency. Indeed, the dependence between the alkyl chain length and the antioxidant efficiency in emulsions usually follow a parabolic shape with a maximum for an intermediate alkyl length derivative (Laguerre et al, 2010(Laguerre et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…This value is not necessary to describe how SIM-53B partitions between the different regions but its knowledge may be important because it delivers insights into the aspects of the reaction mechanism for the reaction between the chemical probe and SIM-53B. The k I value is comparable to that of the value obtained for chlorogenic acid ( k I = 15 mM −1 s −1 ) [ 26 ] but lower for that of, for example, gallic acid ( k I = 53 mM −1 s −1 ) [ 36 ], hydroxytyrosol ( k I = 117 mM −1 s −1 ) [ 29 ] or α-tocopherol ( k I = 190 mM −1 s −1 ) (unpublished results).…”
Section: Resultsmentioning
confidence: 95%
“…For example, at Φ I = 0.005, (SIM I ) changes from 0.17 to 0.2 M upon decreasing the O/W ratio (differences less than 15%), and the differences are much less at higher emulsifier volume fractions (Φ I = 0.045) than at lower emulsifier volume fractions (Φ I = 0.005). Therefore, changes in the oil-in-water ratio should have predictably an almost negligible effect on the antioxidant efficiency of SIM-53B in inhibiting lipid oxidation since the effectiveness of the series of homologous AOs is directly related to their distribution according to our previous work [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation